The Influence Of Brand Awareness, Brand Image, And Brand Trust On The Decision To Purchase HP Laptops In The Jabodetabek Community - Gian Muktabar Anggoro Jati; Afif Zaerofi (SEAN Institute, 2024)
The personal computer industry, especially in the classification of laptop, is one of the largest industries in Indonesia, which has massive sales. In this sector, products from several global-scale computer companies have long been the choice of Indonesian consumers, including HP as its one of leading brand for laptop. This aim to analyze the effect of brand awarness, brand image, brand trust on HP laptop purchasing decisions in Jabodetabek who use HP Laptop. The population in this study were 100 then the whole was taken to be sampled who use HP laptop. Methods of data analysis using the validity and reliability of the questionnaire, multiple regression analysis. The results of this study indicate that the brand awarness, brand image and brand trust variables simultaneously and partially have a significant effect on purchasing decisions (a survey of HP laptop users specifically for the Jabodetabek area). The coefficient of determination is 0.772 which indicates that the ability of the independent variables to predict the dependent variable is 77%. 23% is influenced by other factors not examined by the author